AHI1 mutations cause both retinal dystrophy and renal cystic disease in Joubert syndrome. Issue 4 (9th September 2005) - Parisi, M A; Doherty, D; Eckert, M L; Shaw, D W W; Ozyurek, H; Aysun, S; Giray, O; Al Swaid, A; Al Shahwan, S; Dohayan, N; Bakhsh, E; Indridason, O S; et al.
Abstract : Background: Joubert syndrome (JS) is an autosomal recessive disorder characterised by hypotonia, ataxia, mental retardation, altered respiratory pattern, abnormal eye movements, and a brain malformation known as the molar tooth sign (MTS) on cranial MRI. Four genetic loci have been mapped, with two genes identified ( AHI1 and NPHP1 ). Methods: We screened a cohort of 117 JS subjects for AHI1 mutations by a combination of haplotype analysis and sequencing of the gene, and for the homozygous NPHP1 deletion by sequencing and marker analysis. Results: We identified a total of 15 novel AHI1 mutations in 13 families, including nonsense, missense, splice site, and insertion mutations, with some clustering in the WD40 domains. Eight families were consanguineous, but no single founder mutation was apparent. In addition to the MTS, retinal dystrophy was present in 11 of 12 informative families; however, no subjects exhibited variable features of JS such as polydactyly, encephalocele, colobomas, or liver fibrosis. In contrast to previous reports, we identified two families with affected siblings who developed renal disease consistent with nephronophthisis (NPH) in their 20s. In addition, two individuals with classic NPH were found to have homozygous NPHP1 deletions. Conclusions: Overall, 11% of subjects had AHI1 mutations, while ∼2% had the NPHP1 deletion, representing a total of less than 15% in a large JS cohort. Some preliminary genotype-phenotype correlations are possible, notably the association of renal impairment, specifically NPH, in those with NPHP1 deletions. Subjects with AHI1 mutations may be at risk of developing both retinal dystrophy and progressive kidney disease.